The effects of maize pollen on development and population growth potential of Amblyseius swirskii and Cydnoseius negevi (Acari: Phytoseiidae) in subsequent generations - Mohamed Lamlom; Shimaa F. Fahim; Faten M. Momen (Persian Journal of Acarology)
Diet is an important component of mass-production system of bio-control agents. Thus, using a non-prey diet (such as plant pollen) instead of natural prey could be more cost-effective in mass-production of phytoseiid predatory mites. Therefore, the present study aimed to examine the multigenerational effect of maize, Zea mays L. (Poaceae), pollen diet on life table parameters of Amblyseius swirskii Athias-Henriot and Cydnoseius negevi (Swirski & Amitai) (Acari: Phytoseiidae) reared for one, five and 11 consecutive generations. The predatory mites A. swirskii and C. negevi successfully completed their development on maize pollen for up to 11 generations. In G1, oviposition days, adult longevity, and fecundity showed significantly higher values in the case of C. negevi as compared to A. swirskii. Despite statistically similar oviposition days in the G11, A. swirskii females (44.43 eggs/♀) deposited significantly more eggs than those of C. negevi (40.60 eggs/♀). There were no significant differences in finite rate of increase (λ), intrinsic rate of increase (r), net (R0) and gross (GRR) reproductive rates between the two predatory mites in G1 and G5 (P ≥ 0.05). In G11, individuals of C. negevi had significantly higher values of r (0.181 day−1) and λ (1.198 day−1) compared to those of A. swirskii (r = 0.159 day−1, λ = 1.173 day−1). However, there were no significant differences in R0 and GRR values between A. swirskii (R0 =34.18 offspring, GRR = 39.75 offspring) and C. negevi (R0 = 31.23 offspring, GRR = 35.44 offspring) in G11. In conclusion, maize pollen has a great potential as a suitable and cost-effective diet for developing the mass-production system of A. swirskii and C. negevi on non-prey diets, where the performance of these predators remained to some extent constant across generations.